TYPES AND FUNCTIONS OF ILLOCUTIONARY SPEECH ACTS ON INTER-CHARACTER DIALOGUE IN TILIK SHORT FILMS (Lingua: Jurnal Bahasa dan Sastra, 2022)
This study aims to describe the types and functions of illocutionary speech acts in Tilik's short film. The data in this study are in the form of utterances from the short film Tilik, uploaded by the YouTube channel Ravacana Films. The data analysis stage used the Determining Element Sorting (PUP) technique. The stage of presenting the results of data analysis used informal methods. Based on the research results, there were 5 types of speech acts, namely (1) assertive illocutionary acts which included stating, informing, suspecting, affirming, affirming; (2) directive illocutionary acts include asking, ordering, prohibiting, advising, recommending, urging, suggesting; (3) acts of commissive illocution include offering, saying prayers; (4) expressive illocutionary acts include saying thanks, apologizing, blaming; and (5) declarative illocutionary act, namely giving names. There are 4 functions of illocutionary acts, namely (1) the competitive function includes ordering, asking; (2) convivial functions, namely offering, saying thank you, saying congratulations; (3) collaborative function, namely stating; (4) conflictive functions, namely reprimanding and scolding